If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + k) = -12 (3 * 3 + k * 3) = -12 (9 + 3k) = -12 Solving 9 + 3k = -12 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3k = -12 + -9 Combine like terms: 9 + -9 = 0 0 + 3k = -12 + -9 3k = -12 + -9 Combine like terms: -12 + -9 = -21 3k = -21 Divide each side by '3'. k = -7 Simplifying k = -7
| x+5+2x+5=70 | | 3/5(2x-15)=1/5x | | 3(w+7)-8w=-4 | | 4x+10=45-2x | | 7x=49findx | | 4(5-3)4= | | 7n^2+48n-5=7n+1 | | 2(y-3)=-3(y-3) | | 6+-50/5=-4 | | 3(1+x)=2[5(x+3)-(x+1)] | | 7n^2+488n-5=7n+1 | | 4n-40=7(-2n+n) | | 7x+32=4y | | 16x+36=14x+50 | | 10n^2+15n+8=3n^2 | | 10=2/3+7 | | -80=8(-6+n) | | 2x+46= | | -6x-22=8 | | 10=2/z+7 | | (1/4)x^3-3x=0 | | 3xsquared=6 | | 8=3w+5w | | -b^2-2b=0 | | 3(-7+48(3)+6(3)(7)+7(3)2+8(3)2(7)+(3)2(7)2)= | | 5x-10(x-2)=6 | | 8d+3=19 | | 8. 3(-7+48(3)+6(3)(7)+7(3)2+8(3)2(7)+(3)2(7)2)= | | 9w+43=-2(w+6) | | 2.6a+4.5b-8.2a-(-4.5b)= | | M^2+2m-29=-5 | | 2(w-4)=9w-43 |